Effects of sowing method and herbicide application on growth, yield and water productivity of two wheat cultivars - Ahmed, Bashir; Daffalla, Mohammed; Elmobark, Hassan; Osman, Abusofian; Idris, Amani (Gezira Journal of Agricultural Science, 2018)
Water management and weed control are crucial components in maximizing wheat yield and water productivity. Little research work has been done on the relationship between sowing methods, chemical weed control and wheat varieties. Field experiments were conducted during 2013/14-2014/15 seasons to evaluate the effect of four sowing methods and herbicide application on the performance of two wheat cultivars at the Gezira and New Halfa Research Stations. The experiment was arranged in a split-split plot design with four replicates, the main plots were assigned to herbicide application (sprayed and unsprayed), sub-plots were allocated to sowing methods (broadcasting + ridging, bed-planting, seed drill and wide level disc), and sub-sub-plots were assigned to wheat cultivars (Bohaine and Imam). Results showed that herbicides did not affect the yield and yield components of wheat for both seasons in the Gezira. Irrespective of herbicide application, seed drill resulted in the highest wheat yield for the two seasons. New Halfa results revealed that the crop growth and yield components were significantly affected. However, the two wheat cultivars resulted in higher yield with bed-planting method under sprayed condition. The interaction of herbicide application and bed-plating methods resulted in higher water productivity, which could be attributed to the lower amount of water applied compared to the other treatments. These results indicated that in the Gezira, unsprayed seed drill and wide level disc sowing methods can be used without yield reduction of wheat. Moreover, herbicides application with bed-planting sowing method in both sites can be used to improve water use efficiency. إدارة مياه الري ومكافحة الحشائش هي أحدى العوامل الأساسية لتعظيم انتاجية القمح وزيادة كفاءة مياه الري. أجريت تجارب حقلية خلال موسمي 2013/14 و 2014/15 لتقييم أثر أربعة طرق للزراعة ومبيد الحشائش على انتاجية صنفين من القمح بمحطتي بحوث الجزيرة وحلفا الجديدة. تم استخدام تصميم القطع المنشقة مرتين بأربع مكررات. وضعت معاملات مبيد الحشائش في الأحواض الرئيسية ووضعت طرق الزراعة في الأحواض الفرعية بينما وضعت الأصناف في الأحواض الفرعية . أوضحت النتائج أن مبيد الحشائش لم يؤثر على الإنتاجية ومكوناتها خلال الموسمين بمحطة بحوث الجزيرة. بغض النظر عن مبيد الحشائش، الزراعة في سطور أعطت أعلى انتاجية خلال الموسمين. كذلك أوضحت النتائج بمحطة بحوث حلفا الجديدة أن النمو ومكونات الانتاجية تأثرتا بصورة معنوية، حيث وجد أن صنفي القمح سجلتا أعلى انتاجية باستخدام الزراعة في مساطب والمكافحة الكيميائية للحشائش. إن أثر تفاعل الزراعة في مساطب والمكافحة الكيميائية للحشائش انتجت أعلى كفاءة مياه ري وذلك يمكن مرده لقلة كمية مياه الري المضافة مقارنةً بالمعاملات الأخرى. النتائج أعلاه تشير إلى أن الزراعة في سطور والزراعة باستخدام الدسك العريض يمكن استخدامهما بالجزيرة لإنتاج القمح دون نقص يذكر في الإنتاجية. اضافةً الي ذلك، فان اضافة مبيد الحشائش لطريقة الزراعة في مساطب يمكن أن تحسن من كفاءة استخدام مياه الري في كلا الموقعين.